Robust Multiple Watermarking Technique for Medical Applications using DWT, DCT and SVD - Assini, Imane; Badri, Abdelmajid; Safi, Khadija; Sahel, Aicha; Baghdad, Abdennaceur (Transactions on Engineering and Computing Sciences, 2017)
The security of medical data plays an important role in preserving their integrity and confidentiality. This paper presents a robust multiple watermarking algorithm based on a combination of discrete wavelet transform (DWT), discrete cosine transform (DCT) and singular value decomposition (SVD). In this proposed method, we have inserted three watermark images (a patient image, a doctor image and a fingerprint of the patient) into a single cover medical image. In the insertion phase, the original image is decomposed into the third level of DWT, and then the DCT and SVD transforms are applied on the selected sub bands (HH1, HH2, and HH3). The first watermark goes through the same steps that the original image. Moreover, the second and the third watermarks are decomposed until the second level and the first level by DWT respectively and subsequently transformed by SVD. The singular values of the three watermarks are inserted into the singular values of the original image. The experimental results show that the proposed method gives better performance in terms of capacity, quality and robustness against various attacks compared to other reported techniques.